요추의 병변이 슬관절 전치환술의 결과에 미치는 영향 - 조우신(Woo-Shin Cho); 변성은(Seong-Eun Byun); 윤영선(Young-Sun Yoon); 선지호(Ji-Ho Sun) (The journal of the Korean Orthopaedic Association, 2013)
목적: 요추의 병변이 슬관절 전치환술의 결과에 미치는 영향을 알아보고자 하였다. 대상 및 방법: 2009년 8월부터 2010년 5월까지 퇴행성 슬관절염으로 단일 집도의에 의해 슬관절 전치환술을 시행받은 환자 중 87명 149예를 대상으로 수술 후 1년 및 2년에 Hospital for Special Surgery scale (HSS 점수)과 슬관절 점수, Western Ontario & McMaster Osteoarthritis Index Score (WOMAC 점수)및 Swiss Spinal Stenosis score (SSS 점수)를 측정하여 전향적 방법을 통해 조사하였다. 결과: 수술 전에 비해 슬관절 점수와 HSS 점수 및 WOMAC score는 수술 후에 월등히 향상되었고, 수술 후 1년보다 2년 추시 시 더 많이 향상되었다. 수술 후 SSS 점수와 슬관절 점수의 상관관계는 통계적으로 유의하지 않은 결과를 보인 반면, HSS 점수와 WOMAC 점수 및 슬관절 점수와 HSS 점수의 차이값은 SSS 점수와 뚜렷한 상관관계를 보였다. 결론: 요추의 병변이 슬관절 전치환술 전, 후의 평가에 영향을 주기 때문에 술 후 평가 시 요추의 병변을 반영하는 평가법과 병행하는 것이 바람직하며, 이 중 SSS 점수가 좋은 평가법이라고 생각된다. Purpose: Patients with osteoarthritis of knee joint often concomitantly suffer from degenerative disease of the spine. Furthermore,resulting spinal problems could influence function and pain after total knee arthroplasty (TKA), and hence, cause the results of TKA tobe misinterpreted. The purpose of this prospective study was to evaluate the effect of spinal disorders, as assessed by Swiss SpinalStenosis score (SSS scores), on knee function as assessed by knee scores, the Hospital for Special Surgery scale (HSS scale) andWestern Ontario & McMaster Osteoarthritis Index scores (WOMAC scores) in patients that after TKA. Materials and Methods: One hundred and forty nine osteoarthritic knees of 87 patients were enrolled in this study. All patientsreceived TKA by single surgeon (W-S Cho) from August 2009 to May 2010. Preoperative and postoperative 1- and 2-years HSS scale,Knee, WOMAC, and SSS scores were recorded and analyzed. Results: Postoperative HSS scale, Knee, and WOMAC scores showed marked improvements versus preoperative scores, and scoresat 2 years postoperatively were better than at 1 year postoperatively. No significant correlation was found between postoperativeKnee scores and SSS scores. On the other hand, statistically significant correlations were found between HSS and SSS scores andbetween WOMAC and SSS scores. Interestingly, differences between Knee scores and HSS scores were found to be significantlycorrelated with SSS scores. Conclusion: When evaluating outcome after TKA, spinal problems should be investigated concomitantly. SSS scores appear toprovide a suitable means of assessing spinal problems. KCI Citation Count: 2